Successful Treatment in a Child with Refractory Periungual Warts by Local Hyperthermia: A Case Report - Du L; Cao Z; Liu Z; Zhu X; Zhang C (Dove Medical Press, 2022)
Lingyun Du,* Zhiqiang Cao,* Zhaoyang Liu, Xia Zhu, Chunhong Zhang Department of Dermato-Venereology, The Second Hospital of Shandong University, Jinan, People's Republic of China*These authors contributed equally to this workCorrespondence: Chunhong Zhang, Department of Dermato-Venereology, The Second Hospital of Shandong University, Jinan, People's Republic of China, Tel +86-531-85875027, Fax +86-531-88962544, Email aliu133@163.comAbstract: Periungual wart is a kind of verruca vulgaris that occurs alongside or underlying the nails, which is challenging to treat and prone to recurrence, seriously affecting the quality of patients' life. We report a 6-year-old boy with periungual warts who had experienced various treatments with no improvement and even worsening. Therefore, we tried to treat the patient with local hyperthermia which uses a patented device that has an infrared emission source. The heat generated by infrared rays acts on the local skin surface. The mechanism of this therapy may be to establish a specific immune response against human papillomavirus-infected tissues, thereby facilitating the clearance of human papillomavirus at irradiated and non-irradiated sites. Local hyperthermia has the advantages of non-contact, safety, noninvasive, less pain, and so on. After 5 treatments, the irradiated periungual warts completely cleared after 2 weeks. The unirradiated sites were almost cured after 7 weeks. This case suggests that local thermotherapy has shown great advantages in the treatment of these refractory periungual warts and offers a new and effective therapy in patients with periungual warts.Keywords: child, local hyperthermia, periungual warts, refractory warts